On insignificance - Leone, Massimo, 1975- author.
1 online resource
Keywords: "Focussing on the anthropological consequences of the disappearing of materiality and sensory embodiment, On Insignificance highlights some of the most perturbing patterns of insignificance that have seeped into our everyday lives. Seeking to explain the semiotic causes of feelings of meaningless, Leone posits that caring for the singularities of the world is the most viable way to resist the alienating effects of the digital bureaucratization of meaning. The book will be of interest to scholars of anthropology, cultural studies, semiotics, aesthetics, communication studies and social theory"--